2015
DOI: 10.1111/trf.13394
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a highly automated instrument for the selection of CD34+ cells from mobilized peripheral blood stem cell concentrates

Abstract: Background Cell selection is an important part of manufacturing cellular therapies. A new highly automated instrument, the CliniMACS Prodigy, was evaluated for the selection of CD34+ cells from mobilized peripheral blood stem cell (PBSC) concentrates using monoclonal antibodies conjugated to para-magnetic particles. Methods PBSCs were collected by apheresis from 36 healthy subjects given G-CSF or G-CSF plus plerixafor. CD34+ cells from 11 PBSC concentrates were isolated with the automated CliniMACS Prodigy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…It has been reported that a medium recovery of 71% and medium purity of 97% of CD34 + cells, with a median of 0.04% residual CD3 + cells could be achieved from either BM or MPB by using the CliniMACS device 23 . Similar results were obtained with the automated CliniMACS Prodigy, although CD34 + cell recovery and depletion of CD3 + cells may be lower than with the semi-automated CliniMACS Plus instrument 24, 25…”
Section: Main Textsupporting
confidence: 57%
“…It has been reported that a medium recovery of 71% and medium purity of 97% of CD34 + cells, with a median of 0.04% residual CD3 + cells could be achieved from either BM or MPB by using the CliniMACS device 23 . Similar results were obtained with the automated CliniMACS Prodigy, although CD34 + cell recovery and depletion of CD3 + cells may be lower than with the semi-automated CliniMACS Plus instrument 24, 25…”
Section: Main Textsupporting
confidence: 57%
“…As pioneers in gene therapy manufacturing since the 1990s 22 , we introduced closed-system processing (from flask to bag-based cell culture) as a means to reduce product contamination 23 . These methods continue to be used and optimized for recent immunotherapies, including the manufacture of clinical grade CAR T-cells, TCR- transduced T-cells, mesenchymal stromal cells, and mutivirus specific T-cells 2426 .…”
Section: Discussionmentioning
confidence: 99%
“…These devices are certified for cell therapy applications and globally accepted by regulatory authorities. [14,15] However, the system is costly and has low throughput, which will have its challenges if we are to foresee roll-out of ex vivo gene-modified cell therapies for diseases such as HIV and sickle cell disease where the patient burden is in the millions and is often in lower-to-middle income countries. There is thus an opportunity to address these limitations with more efficient process developments, lower cost and higher throughput equipment solutions.…”
Section: Cell Processingmentioning
confidence: 99%